2019
DOI: 10.2147/ppa.s227780
|View full text |Cite
|
Sign up to set email alerts
|

<p>Preference, Perception And Predictors Of Herbal Medicine Use Among Malay Women In Malaysia</p>

Abstract: BackgroundPreference for herbal use is increasing worldwide. This is especially true for Malay women in Malaysia that is steeped in traditional and cultural values and surrounded by diverse flora. However, concerns arise with the use of herbs due to the lack of monitoring, scientific evidence and risk of adverse effects. As such identifying potential herbal users is vital to ensure appropriate management is optimised.ObjectiveThis study derives insights on preferred herbs, perception and predictors of herbal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 11 publications
(20 reference statements)
3
14
1
Order By: Relevance
“…This is contrary to other studies in which women had a higher probability of using herbal medicine and/or food supplements than men [35]. From this study, the proportion of married and divorced / separated respondents who had ever used HMPs was higher than singles, which agrees with another study where married women were 3.9 times more likely to use herbs than unmarried women [36]. However, other studies indicated no statistically significant associations between a woman's marital status and the use of herbal drugs in pregnancy [37].…”
Section: Discussioncontrasting
confidence: 71%
“…This is contrary to other studies in which women had a higher probability of using herbal medicine and/or food supplements than men [35]. From this study, the proportion of married and divorced / separated respondents who had ever used HMPs was higher than singles, which agrees with another study where married women were 3.9 times more likely to use herbs than unmarried women [36]. However, other studies indicated no statistically significant associations between a woman's marital status and the use of herbal drugs in pregnancy [37].…”
Section: Discussioncontrasting
confidence: 71%
“…Kaempferia galanga belonging to the Zingiberaceae family, is one of the potential medicinal plants endemic to India and distributed across Indonesia (7,8), Laos (9), Sri Lanka (10,11), China (12), Malaysia (13,14), Nigeria (15), Thailand (16,17), Bangladesh (18), Japan (19), Sudan (20), and Vietnam (21). In traditional medicine in Asian countries, this plant is widely used by local practitioners (22).…”
Section: Introductionmentioning
confidence: 99%
“…In general, GP uses herbal and natural products as the rst therapeutic option and believes in herbal products' safety (Alkhamaiseh and Aljofan, 2020;Tengku Mohamad et al, 2019). For this reason, among others, herbs have been used for conditions such as cough symptoms as well as chronic diseases, such as rheumatoid diseases or cancer (Barry, 2018).…”
Section: Introductionmentioning
confidence: 99%